2020
DOI: 10.1098/rspb.2020.2413
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for integrating disparate social information

Abstract: Social information use is widespread in the animal kingdom, helping individuals rapidly acquire useful knowledge and adjust to novel circumstances. In humans, the highly interconnected world provides ample opportunities to benefit from social information but also requires navigating complex social environments with people holding disparate or conflicting views. It is, however, still largely unclear how people integrate information from multiple social sources that (dis)agree with them, and among each other. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 69 publications
10
55
1
Order By: Relevance
“…In fact, in the Sorted and Unsorted treatments, the participants tend to focus their attention on the central tendency of the social information when receiving multiple estimates. This is supported by previous findings [22,29,30], and is consistent with the use of heuristic strategies under time and cognitive constraints [11][12][13].…”
Section: Sensitivity To Social Influencesupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, in the Sorted and Unsorted treatments, the participants tend to focus their attention on the central tendency of the social information when receiving multiple estimates. This is supported by previous findings [22,29,30], and is consistent with the use of heuristic strategies under time and cognitive constraints [11][12][13].…”
Section: Sensitivity To Social Influencesupporting
confidence: 90%
“…We found that subjects follow social information substantially more when receiving the average estimate of other group members (Aggregated treatment), than when receiving a series of their individual estimates (Sorted and Unsorted treatments). Previous studies demonstrated that people are sensitive to the dispersion of estimates, and weigh social information more when the dispersion is low, a mechanism called the 'similarity effect' [22,30]. Possibly, observing the dispersion of the estimates in the Sorted and Unsorted treatments reduced the weight given to the social information as compared to the Aggregated treatment.…”
Section: Discussionmentioning
confidence: 99%
“…showing ingroup and outgroup sources (Fig. S6), confirming previous observations that individuals' social information use tends to be consistent across contexts [28][29][30][31].…”
Section: Social Information Use Markedly Varied Between Individuals and Was Strongly Correlated Across Blockssupporting
confidence: 89%
“…In four rounds, social information showed a lower vote share for the participant's preferred party, and in another four rounds, social information showed a higher vote share. To allow for a constant scope for adjustments and to control for distance effects that might influence adjustments [30,31,53], we held the difference between a participant's first prediction and social information constant at 15-18 percentage points. To enhance believability, the two remaining (filler) rounds, social information was either very close or very far from the participant's first prediction.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…Our third experiment considers how social information shapes belief formation in a context where social values or preferences are irrelevant [31]. In such settings, social information can help individuals acquire useful knowledge [32] and make accurate decisions [33,34], but may also misinform [35], promote beliefs in conspiracy theories [36] or fuel group polarization [37].…”
Section: Prosocialitymentioning
confidence: 99%